2021
DOI: 10.1016/j.heares.2020.108157
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical neural generators of the envelope-following response in sleeping children: A transfer function analysis

Abstract: Multiple auditory structures, from cochlea to cortex, phase-lock to the envelope of complex stimuli. The relative contributions of these structures to the human surface-recorded envelope-following response (EFR) are still uncertain. Identification of the active contributor(s) is complicated by the fact that even the simplest two-tone ( f 1 & f 2 ) stimulus, targeting its ( f 2 − f 1 ) envelope, evokes additional linear ( f 1 & f 2 ) and non-linear ( 2 f 1 − f 2 ) phase-locked components as well as a transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…This further strengthens the previous conclusion about the cochlear nerve origin of EFR-H waveforms in sleeping children proposed by Lucchetti et al (2021).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This further strengthens the previous conclusion about the cochlear nerve origin of EFR-H waveforms in sleeping children proposed by Lucchetti et al (2021).…”
Section: Discussionsupporting
confidence: 91%
“…As it is highly improbable that a brainstem compression by the PFT mass effect would have increased conduction velocities along cochlear nerve axons, the shortened delay must have resulted from decreased processing time. The processing of cochlear nerve inputs by cochlear nucleus neurons leading to enhanced PLV outputs is thought to imply monaural coincidence detection (Lucchetti et al 2021) operated by the so-called high-sync cells found in the ventral part of the nucleus (Recio-Spinoso 2012) and identified as spherical and globular bushy cells as well as octopus cells (Keine & Rübsamen 2015; Lu et al 2018). The current view about signal processing by high-sync neurons is that it is controlled by a dynamic balance between excitation and inhibition (Keine & Rübsamen 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations